2000
DOI: 10.1093/jn/130.7.1780
|View full text |Cite
|
Sign up to set email alerts
|

Coarse Brown Rice Increases Fecal and Large Bowel Short-Chain Fatty Acids and Starch but Lowers Calcium in the Large Bowel of Pigs

Abstract: Young male pigs were fed a diet formulated from human foods including either boiled white rice plus rice bran or heat-stabilized brown rice at equivalent levels of fiber for 3 wk. Stool and starch excretion were low in pigs fed white rice during the first 2 wk of the experiment. In pigs fed brown rice, their excretion was high during wk 1 but declined in wk 2 while short-chain fatty acid (SCFA) excretion was higher at both times. Large bowel digesta mass, measured during wk 3, was higher in pigs fed brown rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 40 publications
4
59
0
Order By: Relevance
“…Sampling procedures have been described in detail (39). Information specific to the experiments described here is given in Supporting Text.…”
Section: Methodsmentioning
confidence: 99%
“…Sampling procedures have been described in detail (39). Information specific to the experiments described here is given in Supporting Text.…”
Section: Methodsmentioning
confidence: 99%
“…Different types of indigestible carbohydrates give rise to different amounts and patterns of CAs during colonic fermentation, and it may therefore be possible to regulate the CA formation by diet. The CAs formed may depend on for example the monomeric composition of the carbohydrates, the type of linkages between the carbohydrate monomers, their solubility and their molecular weight (Berggren et al, 1993;Casterline et al, 1997;Bird et al, 2000;Karppinen et al, 2000;Henningsson et al, 2002Henningsson et al, , 2003Nilsson and Nyman, 2005). Studies examining CA formation have mainly been conducted in vitro by using human faecal inocula, or in vivo using animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining CA formation have mainly been conducted in vitro by using human faecal inocula, or in vivo using animal models. The rat is the most common model when studying the CA formation in vivo, although there are also some studies available in pigs (Berggren et al, 1993;Roland et al, 1995;Brown et al, 1997;Djouzi and Andrieux, 1997;Bird et al, 2000;Henningsson et al, 2002Henningsson et al, , 2003Nilsson and Nyman, 2005). Studies in man have mainly been performed by measurements of CAs in faeces and have been questioned on the premises that such measurements do not give information regarding the formation of CAs in proximal colon where most of the fermentation actually takes place.…”
Section: Introductionmentioning
confidence: 99%
“…In humans it has been demonstrated that administration of an a-amylase inhibitor, acarbose, to subjects resulted in enhanced butyric acid in faeces, measured either as concentration or as percentage of total SCFAs (53). However, studies in rats (54)(55)(56) and pigs (45,57,58) have shown important variations in fermentation profiles for RS. An explanation could be that the production of butyric acid may vary for different sources of RS.…”
mentioning
confidence: 99%